Financial Help for War Victims and Latvian State Institutions by Latvians Abroad, 1917–1921 - Beķere, Kristīne (Acta humanitarica academiae Saulensis, 2025)
Although patriotic Latvians were not a majority among the socially active foreign Latvians, this fact was largely offset by their activity, and the patriotic Latvians achieved significant results. Collecting and sending of financial help to Latvia was one of the areas of activity where these results are most demonstrable. Individual donors addressed their support directly to structures of the Latvian state, such as the Information Office in London or the Latvian delegation at the Paris Peace Conference. However, the majority of consignments was sent to support war victims, people in need and refugees. These resources mainly reached their recipients via the largest relief organisations in Latvia: the Latvian Red Cross, the Latvian Women’s Relief Corps, Latvian War Invalids Society and the Society for the Reevacuation of Latvian Refugees. It is impossible to calculate the exact total amount of the donations; however, the available figures allow one to conclude that the total amount was rather significant. The amount of individual donations sent by organisations tended to be small or medium; however, the total amount of money sent to Latvia by foreign Latvians was large and could – according to hypothetical calculations – even significantly exceed 100,000 Latvian roubles per year (total amount for all organisations). Collecting donations for Latvia not only demonstrated the positive attitude of the particular group of foreign Latvians towards their homeland, but was also a factor that energised the social life of diaspora Latvian communities themselves. A number of new organisations were founded in the USA, Canada and Brazil for collecting donations. The existing organisations also focused their efforts in this area.